Risk factors associated with hypertension induced by pregnancy. - Távara Orozco, Luis (2015)
From 1988 to 1992, 18 732 deliveries were attended in Obstetrics and Gynecology Department of Maria Auxiliadora Hospital. During this period 1,309 women also were attended with preeclampsia and 146 with eclampsia (incidence 7,0% and 0,8% respectively). Using a cases and control investigation we found the next risk factors associated to preeclampsia-eclampsia in patients of Cono Sur of Lima-Perú: age 10-19 years, age 35 years and older, obesity, unmarried, nuliparity, grand multiparity, new pregnancy after 8 years, anemia, multiple pregnancy, cronic hypertension and urinary infection.